HUBUNGAN ANTARA PENGGUNAAN MEDIA KOMIK DENGAN MINAT MEMBACA SISWA SEKOLAH DASAR - Fenty Nurriyah Fahrurohmah, - (2021)
Comic is one of the most popular media among the students. With the development of technology, nowadays comics are increasingly attracting students' attention, whether they can be read in the form of printed comic books or in the form of digital comics. Currently, the use of comics media is not only used in non-formal activities but also in formal activities. Some of the functions of comics are to motivate students to learn and read. Therefore, the purpose of this study was to find out how big the relationship between the use of comics media and the reading interest of elementary school students. Descriptive type of correlation design is used in this research. Data collection was conducted by distribution of closed questionnaires to 52 respondents of sixth grade elementary school students. The collected data were analyze using descriptive percentage and correlation analysis. The result of this research is, 1) the use of comics media in schools is in the good category with a percentage of 71.08%; 2) students' interest in reading is also in the good category with a percentage of 71.82%; 3) there is a positive and significant relationship between the use of comics media and students' reading interest the correlation test obtained 0,236 in the low level relationship category. That is, if the use of comics media by students increases, the students' interest in reading will also increase. However, it is in the low category which means that not all students like comics media and are interested in reading.